Comparison of the impact of SFAs from cheese and butter on cardiometabolic risk factors: a randomized controlled trial. Issue 4 (1st March 2017) - Brassard, Didier; Tessier-Grenier, Maude; Allaire, Janie; Rajendiran, Ethendhar; She, Yongbo; Ramprasath, Vanu; Gigleux, Iris; Talbot, Denis; Levy, Emile; Tremblay, Angelo; Jones, Peter JH; Couture, Patrick; et al.
ABSTRACT: Background: Controversies persist concerning the association between intake of dietary saturated fatty acids (SFAs) and cardiovascular disease risk. Objective: We compared the impact of consuming equal amounts of SFAs from cheese and butter on cardiometabolic risk factors. Design: In a multicenter, crossover, randomized controlled trial, 92 men and women with abdominal obesity and relatively low HDL-cholesterol concentrations were assigned to sequences of 5 predetermined isoenergetic diets of 4 wk each separated by 4-wk washouts: 2 diets rich in SFAs (12.4–12.6% of calories) from either cheese or butter; a monounsaturated fatty acid (MUFA)–rich diet (SFAs: 5.8%, MUFAs: 19.6%); a polyunsaturated fatty acid (PUFA)–rich diet (SFAs: 5.8%, PUFAs: 11.5%); and a low-fat, high-carbohydrate diet (fat: 25%, SFAs: 5.8%). Results: Serum HDL-cholesterol concentrations were similar after the cheese and butter diets but were significantly higher than after the carbohydrate diet (+3.8% and +4.7%, respectively; P < 0.05 for both). LDL-cholesterol concentrations after the cheese diet were lower than after the butter diet (−3.3%, P < 0.05) but were higher than after the carbohydrate (+2.6%), MUFA (+5.3%), and PUFA (+12.3%) diets ( P < 0.05 for all). LDL-cholesterol concentrations after the butter diet also increased significantly (from +6.1% to +16.2%, P < 0.05) compared with the carbohydrate, MUFA, and PUFA diets. The LDL-cholesterol response to treatment was significantly modified by baseline values ( P -interaction = 0.02), with the increase in LDL cholesterol being significantly greater with butter than with cheese only among individuals with high baseline LDL-cholesterol concentrations. There was no significant difference between all diets on inflammation markers, blood pressure, and insulin-glucose homeostasis. Conclusions: The results of our study suggest that the consumption of SFAs from cheese and butter has similar effects on HDL cholesterol but differentially modifies LDL-cholesterol concentrations compared with the effects of carbohydrates, MUFAs, and PUFAs, particularly in individuals with high LDL cholesterol. In contrast, SFAs from either cheese or butter have no significant effects on several other nonlipid cardiometabolic risk factors. This trial was registered at clinicaltrials.gov as NCT02106208.